EFEKTIVITAS PEMBIAYAAN MIKRO SYARIAH DALAM RANGKA PENGEMBANGAN UMKM: Studi Kasus KSPPS Tamzis Bina Utama Jakarta - Alifiah Nandya Putri (2022)
Micro, Small and Medium Enterprises (MSMEs) are said to be one of the business sectors that make a major contribution to the Indonesian economy. In developing the potential of MSMEs, the government emphasizes financial institutions to focus on distributing MSME capital assistance. Islamic microfinance institutions have a main role in providing business development services through micro-scale financing. The purpose of this study is to analyze the distribution scheme of sharia microfinance, analyze the effectiveness of sharia microfinance to MSME members in Tamzis Jakarta and analyze the impact of sharia microfinance distribution for members of Tamzis Jakarta MSMEs. The research method used is a qualitative method with a case study approach. Data collection techniques used interviews, observations and documentation to the Area Manager of KSPPS Tamzis Bina Utama Jakarta and 4 Jambul market traders. The result of this research is that the sharia microfinance distribution scheme is in accordance with the DSN MUI Fatwa No. 07/DSN-MUI/IV/2000 concerning Mudharabah Financing and the DSN MUI Fatwa No. 04/DSN-MUI/IV/2000 concerning Murabahah Financing. The effectiveness of Islamic microfinance disbursement is measured using 5 indicators, namely target accuracy, goal achievement, program socialization, program monitoring and financing procedures have been running effectively and have had a positive impact on the development of MSMEs, especially market traders who are members of KSPPS Tamzis Bina Utama Jakarta.